ANALISIS KAUSALITAS PENGELUARAN SEKTOR PUBLIK DENGAN PEREKONOMIAN DAERAH PROVINSI SUMATERA BARAT (Pendekatan Model Vector Autoregression, VAR) - Hasdi Aimon (Jurnal Riset Manajemen Bisnis dan Publik, 2013)
This study aims to determine the effect of public sector expenditure lag , and the lag of the regional economy to the economy of West Sumatra Province and the lag effect of the regional economy , and the lag of public sector spending on public sector expenditures West Sumatra Province . This research is a quantitative descriptive and associative . The analysis model used in this study is a model of Vector Autoregression ( VAR models ) using simulation ( lag 1 and 2 ) and ( lag 1 , 2 and 3 ) . The simulation results show the model VAR ( lag 1 and 2 ) is more appropriate , because the SIC and AIC is smaller. The results showed that the local economy lag 1 and lag 2 public sector spending significant effect terhadaap West Sumatra provincial economy . While the regional economy lag 1 and lag 1 public sector spending also significantly on public sector spending areas of West Sumatra province . In connection with these results , the study recommends that local governments pursue policies that constantly improve public sector spending so that spending on lag 1 and lag 2 plays a role in the regional economy so that these conditions have a causal effect between public sector spending and the economy of the province of West Sumatra .